Development of Snakes and Ladders Learning Media for Introducing Sex Education to Children Aged 5-6 Years - Anastasya, Amanda; Hasis, Pertiwi Kamariah; Bulu', Rifa'ah Mahmudah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Sexual violence against young children in Indonesia continues to rise, underscoring the need for early preventive education through age-appropriate learning media. This study aimed to develop an interactive snakes and ladders-based medium to introduce basic sex education concepts to children aged 5ÔÇô6. Using the ADDIE development model, the research focused on expert validation stages. Data were collected through interviews, observations, and expert validation questionnaires, then analyzed descriptively. The medium achieved a 92% validity score from content experts and 84% from media experts, indicating high feasibility and relevance for early childhood sex education. Such tools may enhance the quality of early intervention programs and foster safer learning environments for young children.┬á